Factors Influencing The Subjective Well-Being Of Mothers Who Have Hyperactive Children - Nayla, Muthia Rahman (UNIVERSITAS PAKUAN, 2024)
This study aimed to identify the factors that influence the subjective well-being of mothers caring for hyperactive children. The problem faced in this study is the decrease in maternal well-being when caring for hyperactive children. The subjects of the study involved mothers caring for children with hyperactivity disorders from various social and economic backgrounds. Data were collected through interviews and observations, including questions about subjective well-being such as life satisfaction, positive effects, adverse effects, social support, knowledge, time management, physical condition, child behaviour, stress levels, personality, coping strategies, and maternal optimism. The results of this study revealed that lack of social support from family and environment, low knowledge of hyperactivity disorder, time management problems, as well as the mother's physical condition all contribute negatively to maternal subjective well-being. The child's hyperactive behaviour and high levels of difficulty also affect the mother's well-being. Denial of the child's symptoms and the mother's internal problems, such as anxiety and depression, also have a negative impact. However, the study also found that a personality that is resilient to adversity, effective coping strategies, a positive relationship with a hyperactive child, and an optimistic attitude of the mother can improve maternal subjective well-being. These findings emphasize the importance of providing social support, appropriate information, and training in stress management and coping strategies to mothers caring for hyperactive children.